Distinct Microbial Assemblage Structure and Archaeal Diversity in Sediments of Arctic Thermokarst Lakes Differing in Methane Sources - Matheus Carnevali, Paula B.; Herbold, Craig W.; Hand, Kevin P.; Priscu, John C.; Murray, Alison E. (Frontiers in Microbiology, 2018)
Developing an ecological understanding of Arctic thermokarst lake sediment-associated microbial diversity, distributions, and potential activities in a geochemical context is an essential first step towards comprehending the contributions of these systems to greenhouse gas emissions, and understanding how they may shift as a result of long term changes in climate. In light of this, we set out to study microbial diversity and structure in sediments from four shallow thermokarst lakes in the Arctic Coastal Plain of Alaska. Sediments from one of these lakes (Sukok) emit methane (CH4) of thermogenic origin, as expected for an area with natural gas reserves. However, sediments from a lake 10 km to the North West (Siqlukaq) produce CH4 of biogenic origin. Sukok and Siqlukaq were chosen among the four lakes surveyed to test the hypothesis that active CH4-producing organisms (methanogens) would reflect the distribution of CH4 gas levels in the sediments. We first examined the structure of the little known microbial community inhabiting the thaw bulb of arctic thermokarst lakes near Barrow, AK. Molecular approaches (PCR-DGGE and iTag sequencing) targeting the SSU rRNA gene and rRNA molecule were used to profile diversity, assemblage structure, and identify potentially active members of the microbial assemblages. Overall, the potentially active (rRNA dominant) fraction included taxa that have also been detected in other permafrost environments (e.g. Bacteroidetes, Actinobacteria, Nitrospirae, Chloroflexi and others). In addition, Siqlukaq sediments were unique compared to the other sites, in that they harbored CH4-cycling organisms (i.e. methanogenic Archaea and methanotrophic Bacteria), as well as bacteria potentially involved in N cycling (e.g. Nitrospirae) whereas Sukok sediments were dominated by taxa typically involved in photosynthesis and biogeochemical sulfur (S) transformations. This study revealed a high degree of archaeal phylogenetic diversity in addition to CH4-producing archaea, which spanned nearly the phylogenetic extent of currently recognized Archaea phyla (e.g. Euryarchaeota, Bathyarchaeota, Thaumarchaeota, Woesearchaeota, Pacearchaeota, and others). Together these results shed light on expansive bacterial and archaeal diversity in Arctic thermokarst lakes and suggest important differences in biogeochemical potential in contrasting methanogenic Arctic thermokarst lake sediment ecosystems.